Seafood safety and food‐borne zoonoses from fish - O Golden; Andreia Juliana Rodrigues Caldeira; LF Rangel; MJ Santos (EFSA Journal, 2022)
Abstract Parasitic nematodes of the genus Anisakis are the causative agent of anisakiosis, an important fish‐borne zoonosis. Humans are infected through consumption of raw or undercooked fish, contaminated with the parasite. Infection can result in both gastrointestinal and allergic symptoms. There are few reports of anisakiosis in Portugal, but evidence of Anisakis allergy exists, indicating that exposure is occurring in the population. The European Food Risk Assessment Fellowship Programme (EU‐FORA) work programme, entitled: ‘Food safety of fish and zoonoses: fish consumption and microbiological risk assessment and perception, from fisherman to final consumers in Portugal’ was hosted by the Interdisciplinary Centre of Marine and Environmental Research (CIIMAR), in Porto, Portugal. It aimed to gather information on risk perception and attitudes in the Portuguese population to contamination of fish with Anisakis spp. and on their knowledge of methods to prevent infection. In addition, it aimed to examine the risk of anisakiosis in the Portuguese population.